Development of Media Interactive Problem Based Learning Android-Assisted to Improve Student at SMA Negeri 10 Medan - Alexander Sitinjak (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
The aim of this research is to develop learning media using that are valid, practical, and effective to improve students' ability to understand flat Derivative topics. The study was carried out at SMA NEGERI 10 MEDAN. The subjects of this research were students of class XI IPA-1. This research is research and development (R&D) using the ADDIE Model. The data collection technique uses a questionnaire assessment sheet for material experts, teaching material experts, learning practitioners and student responses. The results showed that learning media using Android Studio obtained an average percentage of 91.8% with the criteria of "very valid" according to the assessment of teaching materials experts and based on media material experts obtained an average percentage of 86.5% with the criteria " very valid". Based on the practice of learning carried out by the mathematics teacher getting 91,8% with the "very practical" criteria. Based on the effectiveness assessment of the 35 students, they got an average percentage of 86.5% with the criteria of "very effective". Thus, based on the results of the assessment of material experts, teaching materials experts, learning practitioners, and student effectiveness it can be said that learning media using Android Studiohave been tested as valid, practical and effective for use in learning.